Pengaruh Ekspor dan Impor dalam Pertumbuhan Ekonomi di Provinsi Aceh - Rianti, Rianti; Lizikrina, Reza; Maimunah, Maimunah; Yanti, Wija; Mahrizal, Mahrizal (UNIVERSITAS SERAMBI MEKKAH, 2025)
The aim of this research is to determine the influence of some imports and exports simultaneously and the simultaneous effect on the economic growth of Aceh Province. The influence of imports and exports on the economic growth of Aceh Province is the aim of this research. The aim of this research is to examine the partial and simultaneous influence of imports and exports on the economic development of Aceh Province. The aim of this research is to examine the partial and simultaneous influence of imports and exports on the economic development of Aceh Province. Research methodology descriptive methodology is used .used . secondary data from the Aceh Province Central Statistics Agency​​ Data on imports, exports and development is included in this time series, this time series which covers the years 2014–2022. takes place in 2014–2022 Documentation and a quantitative literature review are the methods utilized to gather information. Using the BPS program, multiple linear regression is used in the research analysis. According to the study's findings, both partial exports and imports have no discernible impact on economic growth, nor do they have any discernible effect on Aceh Province's economic growth.